Associations between metabolic score for visceral fat and adult lung functions from NHANES 2007–2012 - Zhou, Jiacai; You, Linlin; Zhou, Xin; Li, Yuying (Frontiers in Nutrition, 2024)
Obesity is a significant part of the factors affecting lung function, and the assessment of obesity using the Metabolic Score for Visceral Fat (METS-VF) is more precise than other indicators like waist circumference and body mass index. This study investigated the relationship between lung function and METS-VF in NHANES database from 2007 to 2012.The data utilized in this study was obtained from NHANES spanning the years 2007 to 2012. A multivariate linear regression analysis,subgroup analysis,and restricted cubic spline were employed to investigate the association between METS-VF and lung function.In a study involving 4,356 participants, a weighted multiple linear regression model revealed a significant negative association between the METS-VF and FEV1, FVC, FEV1/FVC ratio, and FEF25-75%. However, no association was observed with PEF. When dividing the METS-VF into thirds, participants in the highest third exhibited significantly decreased levels of FEV1 (β: -342, 95%CI: -440, -245, p<0.001), FVC(β: -312, 95%CI: -431, -192, p<0.001), FEV1/FVC(β: -0.020, 95%CI: -0.030, -0.010, p<0.001), and FEF25-75%(β: -424, 95%CI: -562, -285, p<0.001). However, there was no significant relationship with PEF(β: -89, 95%CI: -325, 147, p=0.446). RCS curve indicated a nonlinear negative correlation between METS-VF and FEV1, FVC, and FEV1/FVC. For FEV1, a significant negative correlation was found when the METS-VF < 6.426(β= -158.595, 95%CI: -228.183, -89.007). This negative association became more pronounced when the METS-VF > 6.426(β= -314.548, 95%CI: -387.326, -241.770). For FVC, a negative association was observed when the METS-VF < 6 .401(β= -5.477, 95%CI: -91.655, 80.702), but it did not reach statistical significance. However, METS-VF > 6.401, METS VF and lung function show a significant negative correlation(β= -399.288, 95%CI: -486.187, -312.388). FEV1/FVC showed a negative correlation only before the inflection point (METS-VF<6.263) (β= -0.040, 95%CI: -0.047, -0.032), after the inflection point (METS-VF>6.263), no correlation was found, but there was no statistical significance (β=0.000; 95%CI: -0.006, 0.007), and METS-VF had a linear negative correlation with FEF25-75%. Subgroup analysis showed that the association was consistent across a variety of demographic factors, including age, sex, race, hypertension, and coronary heart disease. In addition, we found a stronger association between men under 40 and lung function.